On the revaluation of property, plant and equipment (ppe): motivations, value relevance, and effects on audit fees - Waresul Karim, A.K.M.; Shariful Islam, M.D.; Bhuyan, R. (Faculty of Management Studies & Commerce, University of Jaffna, 2020)
This paper examines three important aspects of asset revaluations under International Financial Reporting Standards (IFRS). First, it seeks to identify characteristics of firms that choose to employ the revaluation model instead of the cost model while accounting for PP&E. Hypothesizing both opportunistic and efficiency motives, the paper finds that firms with high leverage are more likely to choose the revaluation model, thus confirming contracting cost reasons, analogous to opportunistic motivation. However, the political cost reason of opportunistic motivation does not appear to be significant. On the other hand, our findings support that efficiency motive is highly significant behind asset revaluations, proving that firms with financial slack or those having higher percentage of investment in PPE are highly likely to choose the revaluation model, while those with growth opportunities are not. Second, given the managers' motivations for choosing the revaluation model, we find, using Ohlson (1995) model, that investors do not consider asset revaluation to be value relevant, proving that investors might already be aware of managers' motivation behind the choice. Finally, the paper empirically tests the effects of the use of the revaluation model on audit fees and finds that the choice of the revaluation model leads to a significant increase in audit fees. This finding supports the hypothesis that the use of the revaluation model involves additional audit effort that merits higher audit fees.
Keywords: Motivations; Value relevance; Audit fees